Auditing - Guy, Dan M. (Harcourt Brace Jovanovich, 1996)
The book contains six major parts: The auditing environment; auditing concepts; auditing tools and techniques; the auditing engagenent; reporting responsibilities; and internal, operational, and governmental audits.